Supporting work practices through telehealth: impact on nurses in peripheral regions - Gagnon, Marie-Pierre (BioMed Central, 2011)
BACKGROUND: In Canada, workforce shortages in the health care sector constrain the ability of the health care system to meet the needs of its population and of its health care professionals. This issue is of particular importance in peripheral regions of Quebec, where significant inequalities in workforce distribution between regions has lead to acute nursing shortages and increased workloads. Information and communication technologies (ICTs) are innovative solutions that can be used to develop strategies to optimise the use of available resources and to design new nursing work practices. However, current knowledge is still limited about the real impact of ICTs on nursing recruitment and retention. Our aim is to better understand how work practice reorganization, supported by ICTs, and particularly by telehealth, may influence professional, educational, and organizational factors relating to Quebec nurses, notably those working in peripheral regions. METHODS/DESIGN: First, we will conduct a descriptive study on the issue of nursing recruitment. Stratified sampling will be used to select approximately twenty innovative projects relating to the reorganization of work practices based upon ICTs. Semi-structured interviews with key informants will determine professional, educational, and organizational recruitment factors. The results will be used to create a questionnaire which, using a convenience sampling method, will be mailed to 600 third year students and recent graduates of two Quebec university nursing faculties. Descriptive, correlation, and hierarchical regression analyses will be performed to identify factors influencing nursing graduates' intentions to practice in peripheral regions. Secondly, we will conduct five case studies pertaining to the issue of nursing retention. Five ICT projects in semi-urban, rural, and isolated regions have been identified. Qualitative data will be collected through field observation and approximately fifty semi-structured interviews with key stakeholders. DISCUSSION: Data from both parts of this research project will be jointly analysed using triangulation of researchers, theoretical approaches, methods, and results. Continuous exchanges with decision makers and periodic knowledge transfer activities are planned to facilitate the dissemination and utilization of research results in policies regarding the nursing recruitment and retention.